THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND QUALITY OF LIFE OF PERSONS WITH DISABILITIES IN THE INDONESIAN ASSOCIATION OF PERSONS WITH DISABILITIES (PPDI) BOJONEGORO BRANCH - Selvi Umma Nur Aprilia; Evita Muslima Isnanda Putri; Titik Nuryanti; Wiwik Utami (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Background: People with disabilities still face various social, psychological, and health limitations that can affect their quality of life. Family support is an important factor in improving the welfare of people with disabilities. Objective: This study aims to analyze the relationship between family support and the quality of life of people with disabilities in the Indonesian Disability Association (PPDI) Bojonegoro Branch. Method: The study used a quantitative correlational design with a cross-sectional approach. The study population was 125 PPDI community members and a sample of 56 respondents was determined using the Slovin formula with a simple random sampling technique. Data collection used a family support questionnaire and WHOQOL-BREF. Data analysis was carried out univariately and bivariately using the Spearman rho test with a significance level of p ≤ 0.05. Results: A total of 50% of respondents had good family support and 54% had a good quality of life. The results of the Spearman rho test showed a significant relationship between family support and quality of life (p = 0.000) with a very strong positive correlation strength (r = 0.931). Conclusion: The better the family support received by people with disabilities, the better their quality of life in the PPDI Community, Bojonegoro Branch